Understanding present-day stress in the onshore Canning Basin of Western Australia. Issue 6 (18th August 2021) - Bailey, A. H. E.; Jarrett, A. J. M.; Tenthorey, E.; Henson, P. A.
Abstract: Western Australia's Canning Basin is an underexplored prospective basin with proven petroleum systems and small-scale production. Recently, several formations within deeper depocentres have been investigated for unconventional hydrocarbon resources. Modern petroleum resource evaluation generally depends on an understanding of local and regional stresses that are a primary control over the formation and propagation of induced fractures. There are significant gaps in our understanding of these factors within the Canning Basin. This study characterises the regional stress regime of the onshore Canning Basin and presents modelled present-day stress, allowing for the identification of significant stress heterogeneity and natural fracture barriers. Interpretation of wireline data reveals a present-day state of stress with variation in magnitude and faulting-type. An approximately northeast–southwest regional present-day maximum horizontal stress orientation is interpreted, which is in broad agreement with the Australian Stress Map and previously published data. One-dimensional mechanical earth models, constructed for intervals from 15 Canning Basin wells, highlight the relationship between lithology and stress. Significant changes in stress within and between lithological units, owing to the existence of discrete mechanical units forming numerous inter- and intra-formational stress boundaries, likely to act as natural barriers to fracture propagation, particularly within those units currently targeted for their unconventional resource potential, are interpreted. A strike-slip faulting stress regime is interpreted broadly through the basin. However, when analysed in detail there are three distinct stress zones identified: (1) a transitional reverse- to strike-slip faulting stress regime in the top ∼1 km, (2) a strike-slip faulting stress regime from ∼1 km to ∼3.0 km and (3) a transitional strike-slip to normal faulting regime at depths greater than ∼3.0 km. This study is a component of the Australian Government's Exploring for the Future initiative, which focusses on gathering new data and information about northern Australia's resource potential. KEY POINTS: New stress data, including 15 mechanical earth models, are presented for Western Australia's onshore Canning Basin. Broadly, a strike-slip stress regime with a NE–SW-oriented maximum horizontal orientation is described. Significant stress heterogeneities and natural fracture barriers are identified.